Strengthening Moral Character through the Internalization of Moderate Islam: A Multisite Study in Pesantren-Based Islamic Junior High Schools in Lamongan - Ahmad Kholid Jauhari; Muhammad Arif Syihabuddin (LPPM Universitas KH. A. Wahab Hasbullah, Jombang, Indonesia, 2025)
The phenomenon of moral decline among Indonesian youth highlights the urgency of value-based education capable of shaping students’ character effectively. The internalization of moderate Islam is considered a key strategy in moral development, as it emphasizes balance, justice, tolerance, and moderation. This study aims to explain the process of internalizing moderate Islamic values in fostering students’ morality and to identify its supporting and inhibiting factors. This research employed a qualitative approach with a multi-site design conducted at MTs Hasyim Asy’ari Kembangbahu and MTs Empat Lima Assa’adah Sambeng, Lamongan. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model combined with Robert K. Yin’s cross-site analysis. The findings reveal that the internalization of moderate Islamic values occurs through three stages: value transformation, value transaction, and value transinternalization, which are implemented in classroom learning, extracurricular activities, congregational worship, and regular deliberation. Supporting factors include the pesantren environment, teacher quality, parental involvement, and the use of technology, while inhibiting factors involve difficulties in controlling students due to gadget use, teachers with multiple responsibilities, and diverse student backgrounds. The study concludes that the internalization of moderate Islam serves as a strategic foundation for moral education in madrasah and remains relevant in addressing the challenges of globalization, technological development, and socio-cultural pluralism